2015
DOI: 10.4137/bic.s29318
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Factor–Factor VII Complex as a Key Regulator of Ovarian Cancer Phenotypes

Abstract: Tissue factor (TF) is an integral membrane protein widely expressed in normal human cells. Blood coagulation factor VII (fVII) is a key enzyme in the extrinsic coagulation cascade that is predominantly secreted by hepatocytes and released into the bloodstream. The TF–fVII complex is aberrantly expressed on the surface of cancer cells, including ovarian cancer cells. This procoagulant complex can initiate intracellular signaling mechanisms, resulting in malignant phenotypes. Cancer tissues are chronically expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 117 publications
1
22
0
Order By: Relevance
“…FVII is an enzyme that belongs to the serine protease class [28, 35], whereas FVIII is a protein that is required for the activation of other coagulation factors [36, 37]. The results of the current study showed significant increases in the levels of FVII and FVIII associated with waterpipe and cigarette tobacco smoking.…”
Section: Discussionsupporting
confidence: 57%
“…FVII is an enzyme that belongs to the serine protease class [28, 35], whereas FVIII is a protein that is required for the activation of other coagulation factors [36, 37]. The results of the current study showed significant increases in the levels of FVII and FVIII associated with waterpipe and cigarette tobacco smoking.…”
Section: Discussionsupporting
confidence: 57%
“…MAPKs (ERK, JNK, and p38), as well as Akt, were reported as the upstream regulators of NF-κB [12,13,14]. Therefore, we would like to investigate the role of these protein kinases in hypoxia-induced TF expression.…”
Section: Resultsmentioning
confidence: 99%
“…To survive and grow in a hypoxic microenvironment, cancer cells must undergo a variety of adaptive changes, including metabolic adaptation, increased resistance to apoptosis, and promotion of angiogenesis and metastasis [10]. In addition, hypoxia-induced upregulation of TF and procoagulant activity has been reported in a variety of cancer types, including, breast cancer [11], ovarian cancer [12], glioma cancer [13], and lung cancer [14]. A major mechanism mediating adaptive responses to hypoxia is the regulation of transcription by hypoxia-inducible factor-1α (HIF-1α) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Dr. Koizume and Dr. Miyagi highlight the role of secretory protein tissue factor (TF) and associated cellular signaling as a diagnostic biomarker in several types of cancer including ovarian cancer. 9 Oncogenic signaling alterations also endow cells with resistance to anticancer therapy. Dr. Zonathan Schatz’s review on manipulation of increased oncogenic signaling to therapeutic benefit provides an insight for novel therapeutic intervention that can be designed to target cancer-sustaining and altered growth-promoting signaling that evades current therapeutic regimens.…”
Section: Supplement Aims and Scopementioning
confidence: 99%